2015
DOI: 10.1016/j.ajpath.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Pulmonary Hypertension

Abstract: Pulmonary veno-occlusive disease (PVOD) is an uncommon form of pulmonary hypertension (PH) characterized by progressive obstruction of small pulmonary veins and a dismal prognosis. Limited case series have reported a possible association between different chemotherapeutic agents and PVOD. We evaluated the relationship between chemotherapeutic agents and PVOD. Cases of chemotherapy-induced PVOD from the French PH network and literature were reviewed. Consequences of chemotherapy exposure on the pulmonary vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
66
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(74 citation statements)
references
References 46 publications
2
66
0
6
Order By: Relevance
“…[19]. Alkylating drugs, most frequently related to PVOD development included the following: cyclophosphamide, mitomycin C (MMC) and cisplatin, especially when combined with additional radiotherapy or allogenic steam cell transplantation [19]. The ability of cyclophosphamide to induce PH was confirmed by the authors in animal models [19].…”
Section: Occupational Dependence Of Pvod/pchmentioning
confidence: 80%
See 2 more Smart Citations
“…[19]. Alkylating drugs, most frequently related to PVOD development included the following: cyclophosphamide, mitomycin C (MMC) and cisplatin, especially when combined with additional radiotherapy or allogenic steam cell transplantation [19]. The ability of cyclophosphamide to induce PH was confirmed by the authors in animal models [19].…”
Section: Occupational Dependence Of Pvod/pchmentioning
confidence: 80%
“…The questionnaire also revealed a significantly higher tobacco exposure in PVOD compared to PAH patients (total packyears 33 ± 24.7 vs 8.0 ± 14.3 respectively) [5]. [19]. Alkylating drugs, most frequently related to PVOD development included the following: cyclophosphamide, mitomycin C (MMC) and cisplatin, especially when combined with additional radiotherapy or allogenic steam cell transplantation [19].…”
Section: Occupational Dependence Of Pvod/pchmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple case reports have reported a link between chemotherapeutic agents and radiation therapy with PVOD 10,15 . A recent detailed study of chemotherapy-induced PH from the French PH network was reviewed 15 .…”
mentioning
confidence: 99%
“…A recent detailed study of chemotherapy-induced PH from the French PH network was reviewed 15 . This study found alkylating and alkylating-like agents represent a significant risk factor for the development of PVOD.…”
mentioning
confidence: 99%